The Babylon Bee guide to wokeness : How to take your wokeness to the next level by canceling friends, breaking windows, and burning it all to the ground. (Salem Books, an imprint of Regnery Publishing, 2021)
In this tongue-in-cheek guide to the left's intersectional insanity, the writers of the satirical social media site The Babylon Bee teach examine: how to choose pronouns; how to blame everyone else for your problems; how to show the world how wonderful you are; the art of virtue-signaling; the basics of race, gender, and intersectionality; the truth about American history; problematic books and movies; how to tell if a baby is racist; and more.